2016
DOI: 10.1051/0004-6361/201527850
|View full text |Cite
|
Sign up to set email alerts
|

Radial velocities of K–M dwarfs and local stellar kinematics

Abstract: Aims. The goal of this paper is to present complete radial-velocity data for the spectroscopically selected McCormick sample of nearby K-M dwarfs and, based on these and supplementary data, to determine the space-velocity distributions of late-type stars in the solar neighborhood. Methods. We analyzed nearly 3300 measurements of radial velocities for 1049 K-M dwarfs, that we obtained during the past decade with a CORAVEL-type instrument, with a primary emphasis on detecting and eliminating from kinematic calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 123 publications
1
26
0
Order By: Relevance
“…Our code for calculating peculiar velocities for bowshock stars uses the position, parallax, and proper motion for each star, removes the peculiar solar motion (U,V,W) ⊙ , computes the expected (U,V,W) * for the star's Galactic position given the adopted rotation curve, and computes the peculiar (U,V,W) * pec velocity of the star, i.e., the star's velocity relative to its local standard of rest. Our code reproduces the velocities of over 1000 K-M dwarf stars (Sperauskas, et al 2016) to within 1.1 km s −1 RMS. Uncertainties are propagated by Monte Carlo techniques.…”
Section: Sample Selection For Measuringṁmentioning
confidence: 76%
“…Our code for calculating peculiar velocities for bowshock stars uses the position, parallax, and proper motion for each star, removes the peculiar solar motion (U,V,W) ⊙ , computes the expected (U,V,W) * for the star's Galactic position given the adopted rotation curve, and computes the peculiar (U,V,W) * pec velocity of the star, i.e., the star's velocity relative to its local standard of rest. Our code reproduces the velocities of over 1000 K-M dwarf stars (Sperauskas, et al 2016) to within 1.1 km s −1 RMS. Uncertainties are propagated by Monte Carlo techniques.…”
Section: Sample Selection For Measuringṁmentioning
confidence: 76%
“…has been conducting a long-term RV survey of nearby low-mass stars using several spectrometers. Most data are obtained at the 1.65-m telescope at the Moletai observatory in Lithuania (Sperauskas et al 2016). A CORAVEL-type spectrometer was used to measure the RVs with a typical accuracy of the order of km s −1 and a spectral resolution around 20000.…”
Section: Vues Observationsmentioning
confidence: 99%
“…This star has no metallicity measurement in the literature. Sperauskas et al (2016) reported a radial velocity of −285.9±0.2 km s −1 . Although this star's tangential velocity (11.2 km s −1 ) is less than 200 km s −1 , the Gaia parallax (37.49 ± 0.23 mas) and proper motion, combined with the radial velocity measurement, yield U, V, W=(−114, −262, +12).…”
Section: The Gaia Dr1 Catalogmentioning
confidence: 99%